Pañjābī kahāṇī, sarūpa siddhānta te wikāsa - Uppala, Sawindara Siṅgha, 1924- (Paṭiālā : Pabalikeshana Biūro, Pañjābī Yūnīwarasiṭī, 1995)
Study of Panjabi short story.
Includes bibliographical references.
Mode of access: Internet.
In Panjabi.
Keywords: Short stories, Panjabi -- History and criticism